Calsyntenin 3β Is Dynamically Regulated by Temperature in Murine Brown Adipose and Marks Human Multilocular Fat - Plucińska, Kaja; Jespersen, Naja Z.; Brown, Erin L.; Petersen, Patricia S.; Rupar, Kaja; Nielsen, Søren; Scheele, Camilla; Emanuelli, Brice (Frontiers in Endocrinology, 2020)
Activation of thermogenic adipose tissue is linked to improved metabolic outcomes in mice and humans. Dissipation of energy as heat during thermogenesis relies on sufficient innervation of fat by sympathetic nerve fibers, a process recently proposed to be regulated by the adipose-specific Calsyntenin3b (Clstn3b)-S100b axis. Here we aimed 1) to assess enrichment patterns of CLSTN3b, S100b as well as the previously annotated neuronal CLSTN3a in perirenal brown and subcutaneous white human fat specimens, and 2) to investigate if the novel Clstn3b is dynamically regulated by changes in environmental temperatures and nutritional stress in thermogenic adipose tissues in mice. We provide evidence for CLSTN3b enrichment in multilocular perirenal fat located anatomically in the proximity to both the adrenal gland and sympathetic nerve bundles innervating the kidney in humans. Moreover, transcript levels of CLSTN3b, but not S100b or CLSTN3a, positively correlate with uncoupling protein 1 (UCP1) expression in human adipose tissue. Our results further show that Clsnt3b is preferentially expressed in brown adipocytes and is highly responsive to changes in environmental temperature and obesity state in mice. Collectively, this brief communication highlights CLSTN3b as a hallmark of thermogenic adipose depots in mice and humans.